The Effect of Financing Distribution, Restructuring and Portfolio at Risk (PAR) on PNM Surabaya Branch Office Revenue During the Covid-19 Pandemic - Yusril Ardiansyah; A Dewantoro Marsono (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was conducted at PT PNM Surabaya Branch for the period 2019-2021 aims to examine the influence of the Effect of Financing Distribution, Restructuring, and Portfolio at Risk (PAR) on PNM Surabaya Branch Office Revenue during the Covid-19 Pandemic. Independent variables are Financing Distribution, Restructuring and Portfolio at Risk (PAR). The dependent variable is PNM Surabaya Branch office Revenue. This research design is quantitative research with use of SPSS version 22, secondary data type. The regression analysis testing, anova test and Residuals test. The results show, based on the anova test (T-test), that partially the distribution of financing, restructuring and portfolio at risk (PAR) has a simultaneous effect on revenue. While based on the Multicollinearity Test, Financing Distribution and Portfolio at Risk (PAR) have no significant effect on revenue of PNM Surabaya Branch office. while restructuring has a very significant effect on the revenue of PNM Surabaya branch office